Photocatalytic degradation of tributyltin chloride in water - Reisi, M.R.; Mun, L.K.; Misran, M. (Chemic Publishing Company, 2010)
In this work, photodegradation of tributyltin chloride in water by UV with or without any catalyst, also with different types of TiO 2 and with modified catalyst was investigated. The rate equation and rate constant was determined and compared.